Coating composition containing a polymeric silane coupling agent having an alkoxysilyl group and a mercapto group in the side chain

The coating composition with a polymer-type silane coupling agent and colloid metal oxide particles addresses the hardness and resistance issues of plastic molding in optical components, enhancing adhesion and durability.

JP7626971B2Active Publication Date: 2025-02-05NISSAN CHEM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021016805
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-06
Filing Date
2021-02-04
Publication Date
2025-02-05
Estimated Expiration
2041-02-04

AI Technical Summary

Technical Problem

Plastic molding materials used in optical components like glasses lenses lack sufficient hardness, scratch resistance, solvent resistance, and weather resistance, making them prone to damage and degradation.

Method used

A coating composition containing a polymer-type silane coupling agent with an alkoxylyl group and mercapto group on the side chain, combined with colloid metal oxide particles, enhances adhesion and resistance properties by forming a durable curing membrane.

Benefits of technology

The coating composition improves adhesion, scratch resistance, and transparency while maintaining weather resistance, suitable for optical components such as glasses lenses and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626971000001
    Figure 0007626971000001
  • Figure 0007626971000002
    Figure 0007626971000002
  • Figure 0007626971000003
    Figure 0007626971000003
Patent Text Reader

Abstract

To provide a coating composition excellent in adhesion of an obtained cured film to a substrate, appearance after a weathering test, adhesion after a weathering test, abrasion resistance, and transparency.SOLUTION: A coating composition includes the following (S) constituent and a (T) constituent, where the S constituent is a silane compound, a hydrolysate thereof, or a mixture thereof, the silane compound includes a polymer-type silane coupling agent as a (S1) constituent, the polymer-type silane coupling agent has an alkoxysilyl group and a mercapto group as side chains on a principal chain of an organic compound, and (mercapto group) / (alkoxysilyl group) which is a mole ratio of mercapto groups and alkoxysilyl groups is 2 to 6, the mercapto group equivalent weight is contained by 150 g / mol to 300 g / mol, the (T) constituent is a colloidal metal oxide particle (T3) having an average particle size of 2 nm to 100 nm, and (S) constituent:(T) constituent is contained by a mass ratio of 100:10 to 500. An optical member has a cured film formed from the coating composition on the surface of an optical substrate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a coating composition and an optical element that can form a cured film that is excellent in hardness, transparency, scratch resistance, adhesion, and weather resistance and is useful as an optical element such as an eyeglass lens. [Background technology]

[0002] Plastic molded products are used in large quantities due to their advantages such as light weight, easy processability, and impact resistance. However, they have disadvantages such as insufficient hardness, susceptibility to scratches, susceptibility to solvent attack, static electricity that attracts dust, and insufficient heat resistance. Therefore, when used as eyeglass lenses, window materials, etc., plastic molded products have the practical disadvantages described above compared to inorganic glass molded products. Therefore, it has been proposed to apply a protective coating (protective film) to plastic molded products. A large number of coating compositions have been proposed for use as protective coatings.

[0003] Coating compositions containing organosilicon compounds or their hydrolysates as the main component (resin component or film-forming component) are used for eyeglass lenses to provide hard coatings similar to those of inorganic systems (Patent Document 1).

[0004] Since the scratch resistance of the above coating composition is still unsatisfactory, a coating composition containing a colloidally dispersed silicon dioxide sol has been proposed, and this has also been put to practical use for eyeglass lenses (Patent Document 2).

[0005] A polymer-grafted colloidal silica dispersion has been disclosed in which colloidal silica has methylamino groups, dimethylamino groups, and isopropylamino groups and silyl residues bonded thereto (Patent Document 3). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 52-11261 [Patent Document 2] Japanese Patent Application Publication No. 53-111336 [Patent Document 3] Japanese Patent Application Laid-Open No. 2008-100894 Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention provides a coating composition that provides a cured film having excellent adhesion to a substrate, appearance after a weathering test, adhesion after a weathering test, scratch resistance, and transparency. [Means for solving the problem]

[0008] A first aspect of the present invention is a coating composition comprising the following component (S) and component (T): The component (S) is a silane compound, a hydrolyzate thereof, or a mixture thereof, and the silane compound includes a polymeric silane coupling agent as the component (S1), and the polymeric silane coupling agent has an alkoxysilyl group and a mercapto group as side chains on the main chain of an organic compound, and the molar ratio of the (mercapto group) to the (alkoxysilyl group), i.e., (mercapto group) / (alkoxysilyl group), is 2 to 6, and the mercapto group equivalent is 150 g / mol to 300 g / mol; Component (T) is colloidal metal oxide particles (T3) having an average particle size of 2 nm to 100 nm, The present invention relates to a coating composition characterized by containing the component (S):component (T) in a mass ratio of 100:10 to 500. As a second aspect, the present invention relates to the coating composition according to the first aspect, wherein the alkoxysilyl group on the side chain of the polymeric silane coupling agent of component (S1) is a trimethoxysilyl group, the molar ratio of (mercapto group) to (alkoxysilyl group), (mercapto group) / (alkoxysilyl group), is 3 to 5, and the mercapto group equivalent is 200 g / mol to 250 g / mol. As a third aspect, the silane compound of the component (S) further contains, as the component (S2), (S2-1): [ka] (In formula (1), R 1 is an alkyl group, an aryl group, a halogenated alkyl group, a halogenated aryl group, an alkoxyaryl group, an alkenyl group, or an organic group having an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a ureido group, or a cyano group, and is bonded to a silicon atom by a Si-C bond; R 2 represents an alkoxy group, an acyloxy group, or a halogen atom, and a represents an integer of 0 to 3.) and a silane compound represented by (S2-2): [ka] (In formula (2), R 3 is an alkyl group bonded to a silicon atom by a Si-C bond, and R 4 represents an alkoxy group, an acyloxy group, or a halogen atom; Y represents an alkylene group, an arylene group, an NH group, or an oxygen atom; b represents an integer of 0 to 3; and c is an integer of 0 or 1. As a fourth aspect, the component (S2) may be a silane compound in which a is 0 in the formula (1) as the component (S2-1-1), or a compound in which a is 1 in the formula (1) as the component (S2-1-1) as the component (S2-1-1) 1 a methyl group, or a mixture thereof; and (S2-1-2) a silane coupling agent in which a in formula (1) is 1 and contains an epoxy group, a silane coupling agent in formula (1) in which a is 1 and contains a (meth)acryloyl group, or a mixture thereof, wherein the mass ratio of (S2-1-1):(S2-1-2) is 1:1 to 1:25. According to a fifth aspect, the present invention relates to the coating composition according to the third aspect, which contains (S1):(S2) in a mass ratio of 5:95 to 30:70. As a sixth aspect, the present invention relates to a coating composition according to any one of the first to fifth aspects, wherein the component (T) is an organic solvent dispersion sol of colloidal particles (T3) formed of modified metal oxide colloidal particles having an average particle size of 2 nm to 100 nm, the core of which is metal oxide colloidal particles (T1) having an average particle size of 2 nm to 60 nm, the surface of which is coated with a coating (T2) consisting of acidic oxide colloidal particles having an average primary particle size of 1 nm to 4 nm. As a seventh aspect, the present invention relates to the coating composition according to the sixth aspect, wherein the colloidal particles (T1) are an oxide of at least one metal selected from the group consisting of Ti, Fe, Cu, Zn, Y, Zr, Nb, Mo, In, Sn, Sb, Ta, W, Pb, Bi, and Ce. As an eighth aspect, the coating (T2) is a group consisting of Si, Zr, Sn, Mo, Sb and W. The present invention relates to a coating composition according to a sixth aspect, wherein the metal oxide is an oxide of at least one metal selected from the group consisting of: As a ninth aspect, the present invention relates to the coating composition according to the sixth aspect, wherein the colloidal particles (T1) are a metal oxide consisting of tin oxide-zirconium oxide or a metal oxide consisting of titanium oxide-tin oxide-zirconium oxide, and the coating (T2) is a metal oxide consisting of tin oxide-silicon dioxide. As a tenth aspect, the present invention relates to the coating composition according to any one of the sixth to ninth aspects, in which the surface of the component (T2) is coated with (meth)acryloyloxytrialkoxysilane, ureidopropyltrialkoxysilane, or glycidoxypropyltrialkoxysilane. According to an eleventh aspect, the present invention relates to the coating composition according to any one of the sixth to tenth aspects, in which the component (T) further contains an amine. As a twelfth aspect, the present invention relates to the coating composition according to any one of the first to eleventh aspects, further comprising a metal chelate or a perchlorate as a curing agent. According to a thirteenth aspect, the present invention relates to the coating composition according to any one of the first to twelfth aspects, further comprising a surfactant. According to a fourteenth aspect, the present invention relates to an optical member having a cured film formed on the surface of an optical substrate using the coating composition according to any one of the first to thirteenth aspects. According to a fifteenth aspect, the present invention relates to an optical member according to the fourteenth aspect, further comprising an anti-reflection film on a surface of the optical member. As a sixteenth aspect, a method for producing a silane compound, a hydrolyzate thereof, or a mixture thereof as a component (S), comprising: (a) a step of preparing a silane compound, a hydrolyzate thereof, or a mixture thereof; The present invention relates to a method for producing a coating composition, which includes a step (b) of mixing the component (S) obtained in the step (a) with colloidal metal oxide particles (T3) having an average particle size of 2 nm to 100 nm as the component (T). [Effects of the Invention]

[0009] The present invention is a coating composition comprising, as component (S), a silane compound, its hydrolyzate, or a mixture thereof, and, as component (T), colloidal metal oxide particles having an average primary particle size of 2 nm to 100 nm.

[0010] The present invention contains a polymeric silane coupling agent as component (S). The polymeric silane coupling agent has an organic compound with an organic structure in the main chain and a plurality of alkoxy groups and organic functional groups (mercapto groups) in the side chain. The alkoxy groups can bond with binder components (e.g., other silane coupling agents) contained in the coating composition or with surface hydroxyl groups (e.g., silanol groups) on colloidal metal oxide particles. Furthermore, the mercapto groups can react efficiently with carbon-carbon double bonds and epoxy groups in other binder components.

[0011] Polymeric silane coupling agents have many reactive sites per molecule, which can be expected to improve adhesion. Furthermore, because they are large molecules, they are less volatile when heated and cured, and have excellent film-forming properties. By incorporating a polymeric silane coupling agent into the coating composition that forms the coating film, the polymeric silane coupling agent acts as a starting point to improve bonding with colloidal metal oxides and other binder components (glass or plastic substrates to which the binder bonds), which can be expected to improve adhesion, especially weather-resistant adhesion.

[0012] In addition, in recent years, plastic lenses have become thinner and have a higher refractive index, and sulfur atoms are involved in this higher refractive index. Polymer-type silane coupling agents contain many mercapto groups, and the mercapto groups and the products of their reaction are highly compatible with high refractive index lens materials, which also contributes to improved adhesion. In addition, the inclusion of sulfur Therefore, the refractive index of the coating film itself is high, and even when applied to a high refractive index substrate, it is possible to reduce the occurrence of fringe patterns (interference fringes) caused by the difference in refractive index.

[0013] The coating composition of the present invention can be applied to optical members, such as eyeglass lenses, camera lenses, automobile window glass, computer displays, television displays, and mobile terminal displays. DETAILED DESCRIPTION OF THE INVENTION

[0014] The present invention provides a coating composition comprising the following component (S) and component (T): The component (S) is a silane compound, a hydrolyzate thereof, or a mixture thereof, and the silane compound includes, as the component (S1), a polymeric silane coupling agent having an alkoxysilyl group and a mercapto group as side chains on the main chain of an organic compound, and containing the polymeric silane coupling agent in a molar ratio of (mercapto group) / (alkoxysilyl group)=2 to 6 and a mercapto group equivalent of 150 to 300 g / mol; The component (T) is colloidal metal oxide particles (T3) having an average particle size of 2 to 100 nm, The coating composition contains the component (S):component (T) in a mass ratio of 100:10 to 500.

[0015] The coating composition of the present invention has a solids concentration of 0.1 to 60% by mass, 1 to 50% by mass, or 10 to 45% by mass, where the solids concentration is the total amount of the coating composition excluding the solvent component.

[0016] The polymeric silane coupling agent of component (S1) has a structure in which an alkoxysilyl group and a mercapto group are attached to the side chain of an organic compound. The alkoxysilyl group has three alkoxy groups bonded to the silicon atom, which in turn is bonded to the organic compound. Examples of alkoxy groups include alkoxy groups having 1 to 10 carbon atoms, such as methoxy, ethoxy, propoxy, isopropoxy, and butoxy, with methoxy being particularly preferred. The methoxy group is converted to a hydroxy group through hydrolysis to form a silanol group. The organic compound is a saturated or unsaturated, linear or cyclic hydrocarbon with properties selected from aliphatic and aromatic hydrocarbons, and may contain a linking group such as an ester group, ether group, or amino group. The ester group, ether group, amino group, or the like may be present in one or more molecules, and may also have repeating units. Multiple alkoxysilyl groups and mercapto groups are linked to these organic compounds. The molar ratio of (mercapto group) / (alkoxysilyl group) is 2 to 6, or 3 to 5, and typically 3 or 5. The mercapto group equivalent is 150 g / mol to 300 g / mol, or 200 g / mol to 250 g / mol, and typically 240 g / mol or 210 g / mol. The mercapto group equivalent is the mass of the silane coupling agent per mole of mercapto group. The viscosity is 500 mm 2 / s~10000mm 2 / s, or 1000mm 2 / s~8000mm 2 / s, typically 1500mm 2 / s, 5000mm 2As these polymer-type silane coupling agents, trade names X-12-1154 and X-12-1156 manufactured by Shin-Etsu Chemical Co., Ltd. can be used.

[0017] The product name X-12-1154 manufactured by Shin-Etsu Chemical Co., Ltd. has a molar ratio of (mercapto group) / (methoxysilyl group)=3 and a viscosity of 1500mm 2 / s, a mercapto group equivalent of 240 g / mol. The product name X-12-1156 manufactured by Shin-Etsu Chemical Co., Ltd. has a molar ratio of (mercapto group) / (methoxysilyl group)=5 and a viscosity of 5000mm 2 / s, a mercapto group equivalent of 210 g / mol. The product is available in a concentration of approximately 15% by weight, for example dissolved in an ethanol solution. They can be diluted with ethanol or used at their original concentrations.

[0018] In the present invention, the component (S) can be used in combination with the component (S1) and the component (S2). The component (S2) may contain at least one silane compound selected from the group consisting of (S2-1) and (S2-2).

[0019] (S2-1) is shown in equation (1), and R 1 is an alkyl group, an aryl group, a halogenated alkyl group, a halogenated aryl group, an alkoxyaryl group, an alkenyl group, or an organic group having an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a ureido group, or a cyano group, and is bonded to a silicon atom by a Si-C bond; R 2 represents an alkoxy group, an acyloxy group, or a halogen atom; and a represents an integer of 0 to 3.

[0020] (S2-2) is shown in equation (2), and R 3 is an alkyl group bonded to a silicon atom by a Si-C bond, and R4 represents an alkoxy group, an acyloxy group, or a halogen atom; Y represents an alkylene group, an arylene group, an NH group, or an oxygen atom; b represents an integer of 0 to 3; and c is an integer of 0 or 1.

[0021] The alkyl group is an alkyl group having 1 to 10 carbon atoms, and examples thereof include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, a cyclopropyl group, an n-butyl group, an i-butyl group, an s-butyl group, a t-butyl group, a cyclobutyl group, a 1-methyl-cyclopropyl group, a 2-methyl-cyclopropyl group, an n-pentyl group, a 1-methyl-n-butyl group, a 2-methyl-n-butyl group, a 3-methyl-n-butyl group, a 1,1-dimethyl-n-propyl group, a 1,2-dimethyl-n-propyl group, a 2,2-dimethyl-n-propyl group, a 1-ethyl -n-Propyl, cyclopentyl, 1-methylcyclobutyl, 2-methylcyclobutyl, 3-methylcyclobutyl, 1,2-dimethylcyclopropyl, 2,3-dimethylcyclopropyl, 1-ethylcyclopropyl, 2-ethylcyclopropyl, n-hexyl, 1-methylpentyl, 2-methylpentyl, 3-methylpentyl, 4-methylpentyl, 1,1-dimethylbutyl, 1,2-dimethylbutyl, 1,3-dimethylbutyl group, 2,2-dimethyl-n-butyl group, 2,3-dimethyl-n-butyl group, 3,3-dimethyl-n-butyl group, 1-ethyl-n-butyl group, 2-ethyl-n-butyl group, 1,1,2-trimethyl-n-propyl group, 1,2,2-trimethyl-n-propyl group, 1-ethyl-1-methyl-n-propyl group, 1-ethyl-2-methyl-n-propyl group, cyclohexyl group, 1-methyl-cyclopentyl group, 2-methyl-cyclopentyl group, 3-methyl-cyclopentyl group, 1-ethyl-cyclobutyl group, 2-ethyl-cyclobutyl group group, 3-ethyl-cyclobutyl group, 1,2-dimethyl-cyclobutyl group, 1,3-dimethyl-cyclobutyl group, 2,2-dimethyl-cyclobutyl group, 2,3-dimethyl-cyclobutyl group, 2,4-dimethyl-cyclobutyl group, 3,3-dimethyl-cyclobutyl group, 1-n-propyl-cyclopropyl group, 2-n-propyl-cyclopropyl group, 1-i-propyl-cyclopropyl group, 2-i-propyl-cyclopropyl group, 1,2,2-trimethyl-cyclopropyl group, 1,2,3-trimethyl-cyclopropyl group, 2,2,Examples include a 3-trimethyl-cyclopropyl group, a 1-ethyl-2-methyl-cyclopropyl group, a 2-ethyl-1-methyl-cyclopropyl group, a 2-ethyl-2-methyl-cyclopropyl group, and a 2-ethyl-3-methyl-cyclopropyl group.

[0022] Furthermore, examples of the alkylene group include alkylene groups derived from the above-mentioned alkyl groups.

[0023] Examples of the aryl group include a phenyl group, a naphthyl group, and an anthryl group. The arylene group is a group derived from the above aryl group, and examples thereof include a phenylene group, a naphthylene group, and an anthrylene group.

[0024] The alkoxy group may be an alkoxy group having 1 to 10 carbon atoms, such as a methoxy group, an ethoxy group, an n-propoxy group, an i-propoxy group, an n-butoxy group, an i-butoxy group, an s-butoxy group, a t-butoxy group, an n-pentyloxy group, a 1-methyl-n-butoxy group, a 2-methyl-n-butoxy group, a 3-methyl-n-butoxy group, a 1,1-dimethyl-n-propoxy group, a 1,2-dimethyl-n-propoxy group, a 2,2-dimethyl-n-propoxy group, a 1-ethyl-n-propoxy group, an n-hexyloxy group, and the like.

[0025] The acyloxy group includes an acyloxy group having 2 to 10 carbon atoms, such as a methylcarbonyloxy group, an ethylcarbonyloxy group, an n-propylcarbonyloxy group, an i-propylcarbonyloxy group, an n-butylcarbonyloxy group, an i-butylcarbonyloxy group, an s-butylcarbonyloxy group, a t-butylcarbonyloxy group, an n-pentylcarbonyloxy group, a 1-methyl-n-butylcarbonyloxy group, a 2-methyl-n-butylcarbonyloxy group, a 3-methyl-n-butylcarbonyloxy group, a 1,1-dimethyl-n-propylcarbonyloxy group, a 1,2-dimethyl-n-propylcarbonyloxy group, a 2,2-dimethyl-n-propylcarbonyloxy group, a 1-ethyl-n-propylcarbonyloxy group, an n-hexylcarbonyloxy group, a 1-methyl-n-pentylcarbonyloxy group, and a 2-methyl-n-pentylcarbonyloxy group.

[0026] The halogen atoms include fluorine, chlorine, bromine, iodine, and the like.

[0027] Examples of the component (S2) include compounds represented by the following formulas (3-1) to (3-10). [ka] [ka]

[0028] Above R 12 is R shown in formula (1) and formula (2). 2 and R 4 The hydrolyzable groups shown in

[0029] In the present invention, the component (S2) is a silane compound in which a is 0 in the formula (1) as the component (S2-1-1), and a compound in which a is 1 in the formula (1) as the component (S2-1-1) is a silane compound in which R 1is a methyl group, or a mixture thereof, and (S2-1-2) is a silane coupling agent in which a in formula (1) is 1 and contains an epoxy group, or a silane coupling agent in formula (1) in which a is 1 and contains a (meth)acryloyl group, or a mixture thereof, and the mass ratio of (S2-1-1):(S2-1-2) can be 1:1 to 1:25.

[0030] As the component (S2-1-1), examples of the silane compound in which a is 0 in formula (1) include tetramethoxysilane and tetraethoxysilane. 1 Examples of the silane coupling agent in which is a methyl group include methyltrimethoxysilane and methyltriethoxysilane.

[0031] As the component (S2-1-2), examples of the silane coupling agent in which a is 1 in formula (1) and contains an epoxy group include glycidoxypropyltrimethoxysilane, glycidoxypropyltriethoxysilane, etc. Examples of the silane coupling agent in which a is 1 in formula (1) and contains a (meth)acryloyl group include methacryloxypropyltrimethoxysilane, methacryloxypropyltriethoxysilane, etc.

[0032] The hydrolysis can be carried out using a hydrolysis catalyst, or can be carried out without a hydrolysis catalyst. When a hydrolysis catalyst is used, 0.001 to 10 moles, preferably 0.001 to 1 mole, of the hydrolysis catalyst can be used per mole of the hydrolyzable group. The reaction temperature for carrying out the hydrolysis is usually 20°C to 120°C. The hydrolysis may be complete or partial. That is, in the coating composition, the silane compound exists as a monomer or a hydrolyzate, but a portion of the silane compound may form a hydrolyzed condensate. In the coating film, the hydrolyzed condensate functions as a binder, and the hydrolyzed condensate forms a network to form a cured film. A catalyst can be used in the hydrolysis and condensation.

[0033] The hydrolysis catalyst may be a metal chelate compound, an organic acid, an inorganic acid, an organic base, or an inorganic base. Some examples include:

[0034] Examples of the metal chelate compound as the hydrolysis catalyst include the chelate compounds described below.

[0035] Examples of organic acids that can be used as hydrolysis catalysts include acetic acid, propionic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, oxalic acid, maleic acid, methylmalonic acid, adipic acid, sebacic acid, gallic acid, butyric acid, mellitic acid, arachidonic acid, shikimic acid, 2-ethylhexanoic acid, oleic acid, stearic acid, linoleic acid, linolenic acid, salicylic acid, benzoic acid, p-aminobenzoic acid, p-toluenesulfonic acid, benzenesulfonic acid, monochloroacetic acid, dichloroacetic acid, trichloroacetic acid, trifluoroacetic acid, formic acid, malonic acid, sulfonic acid, phthalic acid, fumaric acid, citric acid, tartaric acid, and trifluoromethanesulfonic acid.

[0036] Examples of inorganic acids that can be used as hydrolysis catalysts include hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, and phosphoric acid.

[0037] Examples of organic bases as hydrolysis catalysts include pyridine, pyrrole, piperazine, pyrrolidine, piperidine, picoline, trimethylamine, triethylamine, monoethanolamine, diethanolamine, dimethylmonoethanolamine, monomethyldiethanolamine, triethanolamine, diazabicyclooctane, diazabicyclononane, diazabicycloundecene, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, etc. Examples of inorganic bases include ammonia, sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, etc.

[0038] Examples of organic solvents used in the hydrolysis include aromatic hydrocarbon solvents, monoalcohol solvents, polyhydric alcohol solvents, ketone solvents, ether solvents, ester solvents, nitrogen-containing solvents, sulfur-containing solvents, etc. These solvents can be used alone or in combination of two or more. Among these, alcohol-based solvents are preferred, and from this perspective, methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, sec-butanol, t-butanol, etc. These organic solvents in component (S) can be used as the organic solvent in the coating composition of the present invention.

[0039] In the present invention, the above (S1):(S2) can be contained in a mass ratio of 5:95 to 30:70.

[0040] In the present invention, the component (T) is colloidal metal oxide particles (T3) having an average primary particle size of 2 nm to 100 nm. The component (T) can be used in the form of a sol containing colloidal metal oxide particles (T3). The sol containing colloidal metal oxide particles (T3) can be an organic solvent sol obtained by substituting an aqueous sol with an organic solvent. The sol can be used at a concentration of 0.1% to 40% by mass, 1% to 30% by mass, or 1% to 20% by mass as the metal oxide.

[0041] Examples of such organic solvents include alcohol-based organic solvents, ether-based organic solvents, ketone-based organic solvents, ester-based organic solvents, aliphatic hydrocarbon-based organic solvents, aromatic hydrocarbon-based organic solvents, and amide compound-based organic solvents.

[0042] Examples of the alcohol-based organic solvent include methyl alcohol, ethyl alcohol, Examples of the alcohol include monohydric alcohols such as propyl alcohol, isopropyl alcohol, butyl alcohol, and isobutyl alcohol; polyhydric alcohols such as ethylene glycol, diethylene glycol, propylene glycol, glycerin, trimethylolpropane, and hexanetriol; and monoethers of polyhydric alcohols such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, and propylene glycol monobutyl ether.

[0043] Examples of the ether-based organic solvent include, in addition to the above-mentioned monoethers of polyhydric alcohols, polyhydric alcohol ethers in which all of the hydroxyl groups of polyhydric alcohols have been alkyl-etherified, such as ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dipropyl ether, ethylene glycol dibutyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, propylene glycol dibutyl ether, diethylene glycol dimethyl ether, diethylene glycol methyl ethyl ether, and diethylene glycol diethyl ether; tetrahydrofuran, 1,4-dioxane, and anisole.

[0044] Examples of the ketone organic solvent include acetone, methyl ethyl ketone, methyl isobutyl ketone, and methyl isoamyl ketone.

[0045] Examples of the ester-based organic solvent include methyl acetate, ethyl acetate, and butyl acetate.

[0046] Examples of the aliphatic hydrocarbon organic solvent include hexane, heptane, octane, nonane, and decane.

[0047] Examples of the aromatic hydrocarbon organic solvent include benzene, toluene, and xylene.

[0048] Examples of the amide compound-based organic solvent include dimethylformamide, dimethylacetamide, and N-methylpyrrolidone.

[0049] Among the above solvents, the following are preferred because they are easily miscible with water: alcohol-based organic solvents such as methanol, ethanol, isopropanol, and butanol; ether-based organic solvents such as ethylene glycol monomethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, and propylene glycol monoethyl ether; ketone-based organic solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; and amide compound-based organic solvents such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone. The organic solvents may be used alone or in combination of two or more.

[0050] These organic solvents in component (T) can be used as the organic solvent in the coating composition of the present invention. When the coating composition of the present invention contains component (S) and component (T), if component (T) is an organic solvent dispersion sol of colloidal metal oxide particles (T3), this organic solvent can be used as the solvent for the coating composition.

[0051] The component (T) is an organic solvent dispersion sol of colloidal particles (T3) formed of modified metal oxide colloidal particles having an average particle size of 2 nm to 100 nm, the core of which is a metal oxide colloidal particle (T1) having an average particle size of 2 nm to 60 nm, the surface of which is coated with a coating (T2) consisting of acidic oxide colloidal particles having an average primary particle size of 1 nm to 4 nm.

[0052] The average particle size can be determined by dynamic light scattering using a dynamic light scattering measuring device (nm). The average primary particle diameter can be determined by observation with a transmission electron microscope (nm).

[0053] The colloidal particles (T1) may be an oxide of at least one metal selected from the group consisting of Ti, Fe, Cu, Zn, Y, Zr, Nb, Mo, In, Sn, Sb, Ta, W, Pb, Bi, and Ce. For example, TiO2, Fe2O3, CuO, ZnO, Y2O3, ZrO2, Nb2O5, NbO2, Nb2O3, MoO2, MoO3, In2O3, SnO2, Sb2O3, Sb2O5, Ta2O5, W2O3, WO2, WO3, PbO, Pb2O4, PbO2, Bi2O3, CeO2, and Ce2O3 may be used alone. Furthermore, these metal oxides may be used in combination of two, three, or more. For example, a combination of ZrO2-SnO2 or a combination of TiO2-SnO2-ZrO2 may be used.

[0054] The coating (T2) can be an oxide of at least one metal selected from the group consisting of Si, Zr, Sn, Mo, Sb, and W. For example, SiO2, ZrO2, SnO2, MoO2, MoO3, Sb2O3, Sb2O5, etc. can be used alone. Furthermore, these metal oxides can be used in combination of two, three, or more. For example, SnO2-SiO2, SnO2-SiO2-Sb2O5, etc. can be used.

[0055] The colloidal particles (T1) are preferably a metal oxide consisting of tin oxide-zirconium oxide or a metal oxide consisting of titanium oxide-tin oxide-zirconium oxide, and the coating material (T2) is preferably, for example, a metal oxide consisting of tin oxide-silicon dioxide.

[0056] The colloidal metal oxide particles (T3) of component (T) having an average particle size of 2 nm to 100 nm can be used with or without coating the surface of the metal oxide particles with a surface coating agent such as a silane coupling agent.

[0057] When (T1) is used alone, or when (T1) is used as a core and coated with (T2) to form a core-shell structure, each can be coated with a silane coupling agent.

[0058] When used in a core-shell structure, the surface of the outermost layer, component (T2), can be coated with (meth)acryloyloxytrialkoxysilane, ureidopropyltrialkoxysilane, or glycidoxypropyltrialkoxysilane. The alkoxy group used can be a methoxy group or an ethoxy group.

[0059] For example, when (T1) is a metal oxide consisting of tin oxide-zirconium oxide and (T2) is a metal oxide consisting of tin oxide-silicon dioxide, and they are coated with (meth)acryloyloxytrialkoxysilane, the particle surface can be surface-treated with (meth)acryloyloxytrialkoxysilane at a rate of 0.2 particles / nm to 1.5 particles / nm, typically 1.0 particles / nm.

[0060] In addition, (T1) is a metal oxide consisting of titanium oxide-tin oxide-zirconium oxide, ( When T2) is a metal oxide consisting of tin oxide and silicon dioxide and is coated with ureidopropyltrialkoxysilane, the particle surface can be surface-treated with ureidopropyltrialkoxysilane at a rate of 0.2 to 1.5 particles / nm, typically 0.5 particles / nm.

[0061] When the colloidal metal oxide particles (T3) of component (T) having an average particle size of 2 to 100 nm are used as a sol dispersed in an organic solvent, they may contain an amine, which improves the stability of the sol.

[0062] Examples of amines include alkylamines such as ethylamine, triethylamine, isopropylamine, and n-propylamine, aralkylamines such as benzylamine, alicyclic amines such as piperidine, and alkanolamines such as monoethanolamine and triethanolamine. Two or more of these can be mixed and contained. These can be contained in an amount of about 30% by mass or less, for example, 0.1 to 30% by mass, based on the total amount of all metal oxides.

[0063] The coating composition of the present invention may contain a metal chelate, a perchlorate, or a mixture thereof as a curing agent. These may be added in an amount of 0.01 to 20% by mass based on the solid content. For example, a metal chelate compound may be added in an amount of 2 to 20% by mass, and a perchlorate may be added in an amount of 0.01 to 2% by mass.

[0064] Examples of metal chelate compounds include titanium chelate compounds such as triethoxy mono(acetylacetonato)titanium, tri-n-propoxy mono(acetylacetonato)titanium, tri-i-propoxy mono(acetylacetonato)titanium, and tri-n-butoxy mono(acetylacetonato)titanium; zirconium chelate compounds such as triethoxy mono(acetylacetonato)zirconium, tri-n-propoxy mono(acetylacetonato)zirconium, tri-i-propoxy mono(acetylacetonato)zirconium, and tri-n-butoxy mono(acetylacetonato)zirconium; and aluminum chelate compounds such as tris(acetylacetonato)aluminum and tris(ethylacetoacetate)aluminum. Perchlorates include aluminum perchlorate nonahydrate.

[0065] The coating composition of the present invention may contain a cationic, anionic, or nonionic surfactant as a surfactant. Examples of nonionic surfactants include silicone surfactants, acrylic surfactants, and fluorine-containing surfactants.

[0066] Examples of fluorine-based surfactants include surfactants having a perfluoroalkyl group, such as perfluoroalkyl sulfonic acid and perfluoroalkyl carboxylic acid.

[0067] Examples of silicone surfactants include polydimethylsiloxanes whose side chains or main chain ends are modified with various substituents such as oligomers of ethylene glycol, propylene glycol, etc., and polyether-modified silicone surfactants.

[0068] The acrylic surfactant is preferably a copolymer of an acrylic monomer, and examples of copolymerizable surfactants include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, octadecyl (meth)acrylate, and hexadecyl (meth)acrylate; benzyl (meth)acrylate; naphthyl (meth)acrylate; and 2-hydroxy-4-methacryloyloxyethoxybenzophenone. (meth)acrylic acid alkyl esters containing aromatic groups such as 3-(2H-1,2,3-benzotriazol-2-yl)-4-hydroxyphenethyl-(meth)acrylate; (meth)acrylic acid alkylene oxide esters such as 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate; (meth)acrylic acid alkylene oxide esters of monools or diols with 2 to 10 moles of alkylene oxide such as triethylene glycol monoethyl ether mono(meth)acrylate, tetraethylene glycol monoethyl ether mono(meth)acrylate, pentaethylene glycol monobutyl ether mono(meth)acrylate, methoxytrioxypropylene tetraoxyethylene (meth)acrylate, and mono(meth)acrylate of an ethylene oxide 6 mole adduct of tetrapropylene glycol; (meth)acrylic acid aminoalkyl esters such as alkyl acrylate ether esters, aminoethyl acrylate, and diethylaminoethyl methacrylate; (meth)acrylic acid amide compounds such as (meth)acrylamide, α-phenyl(meth)acrylamide, N-isopropyl(meth)acrylamide, Nt-octyl(meth)acrylamide, Nn-octyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-ethoxymethyl(meth)acrylamide, N,N'-methylenebis((meth)acrylamide), N-diacetone(meth)acrylamide, N-(n-butoxymethyl)(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, and (meth)acryloylmorpholine.

[0069] The coating composition of the present invention may further contain the organic solvent used in the component (S) or component (T) described above, in addition to the organic solvent derived from the component (S) or the organic solvent derived from the component (T).

[0070] The coating composition of the present invention can be applied to a substrate to form a cured film. By using a substrate with transparency suitable for optical applications, an optical substrate having a cured film can be obtained.

[0071] The coating composition can be cured by heat drying or by irradiation with active energy rays. The heat drying conditions are preferably 70°C to 200°C, more preferably 80°C to 150°C. A cured film is obtained after a heat curing time of 0.5 to 5 hours, or 1 to 3 hours. Heat drying is preferably carried out in hot air. Examples of active energy rays include infrared rays, ultraviolet rays, and electron beams. Far infrared rays, in particular, can minimize heat damage.

[0072] The coating composition of the present invention can be applied to a substrate by a commonly used method such as dipping, spinning, spraying, etc. The dipping and spinning methods are particularly preferred.

[0073] Furthermore, before applying the coating composition of the present invention to a substrate, the adhesion between the substrate and the cured film can be improved by chemical treatment with an acid, alkali, various organic solvents or detergents, or physical treatment with plasma, ultraviolet light, etc. Furthermore, the adhesion between the substrate and the cured film can be further improved by performing a primer treatment using various resins.

[0074] Furthermore, the cured film formed from the coating composition of the present invention can be used as an anti-reflection film as a high refractive index film, and can also be used as a multifunctional film by adding components having functions such as anti-fogging, photochromic, and anti-fouling properties.

[0075] The optical component having a cured film formed from the coating composition of the present invention is a spectacle lens. In addition, it can be used in camera lenses, automobile window glass, and optical filters attached to liquid crystal displays and plasma displays.

[0076] The optical element of the present invention has a cured film formed from the coating composition of the present invention on the surface of the optical substrate, and an antireflection film made of a vapor-deposited film of an inorganic oxide can be formed on the cured film. [Example]

[0077] 〔viscosity〕 Measured using an Ostwald viscometer (25°C). 〔moisture〕 It was determined by Karl Fischer titration. [Average particle size measured by dynamic light scattering (dynamic light scattering particle size): Unit: nm] The sol was diluted with a dispersion solvent, and the parameters of the solvent were used to measure the dispersion using a dynamic light scattering measurement device: Zeta-sizer manufactured by Malvern Instruments Ltd. [Average primary particle size measured by transmission electron microscope: Unit: nm] The sol was dropped onto a copper mesh and dried, and observed using a transmission electron microscope (JEOL JEM-1020) at an accelerating voltage of 100 kV. The average value of 100 particles was measured and calculated as the primary particle size. (1) Adhesion test A cured film formed on a urethane plastic lens substrate was cross-cut at 1 mm intervals to 100 holes, and adhesive tape (cellophane tape, product of Nichiban Co., Ltd.) was firmly attached to the cross-cut areas, and then the adhesive tape was quickly peeled off, and the presence or absence of peeling of the cured film after peeling off the adhesive tape was checked. The evaluation criteria are as follows: A: No peeling at all or peeling of less than 5 out of 100 stitches is observed. B: Peeling is confirmed in 5 to 30 of 100 stitches C: Peeling is confirmed in 31 to 60 of 100 stitches D: Peeling can be confirmed at 61 to 90 of 100 stitches. E: Peeling can be confirmed on 91 or more of 100 stitches. (2) Changes in appearance after weather resistance testing A cured film formed on a urethane plastic lens substrate was exposed to a xenon weather meter (irradiation intensity 40 mW / m 2The cured film after exposure was visually inspected for cracks. (3) Adhesion test after weather resistance test A cured film formed on a urethane plastic lens substrate was exposed to a xenon weather meter (irradiation intensity 40 mW / m 2 The cured film was exposed to light for 100 hours using a 100% acrylic adhesive tape. After exposure, a cross-cut was made on the cured film, and a test similar to that in (1) Adhesion Test was carried out to check for peeling of the cured film after peeling off the adhesive tape. The evaluation criteria used were those in (1) Adhesion Test. (4) Scratch resistance test The surface of the cured film formed on a urethane-based plastic lens substrate was rubbed with steel wool #0000, and the cured film was visually inspected for scratches in a bright room under fluorescent light. The scratch resistance test was conducted once per 10 seconds with a load of 1 kg or more. The evaluation criteria were as follows: A: No scratches can be seen at all B: Some scratches can be seen C: Visible scratches can be seen (5) Transparency test The cured film formed on the urethane plastic substrate was visually inspected in a dark room under fluorescent light for cloudiness. The evaluation criteria were as follows: A: Almost no fogging occurs B: Cloudiness occurs, but to the extent that it does not pose a problem as a transparent cured film. C: Significant bleaching (6) Refractive index The reflectance of the cured film formed on the glass substrate was measured using a reflectance measuring device (USPM-RU manufactured by Olympus Corporation). The refractive index of the cured film was calculated from the measured reflectance using optical simulation.

[0078] (Reference example 1) Preparation of core colloidal particles of zirconium oxide and stannic oxide (T1-1) 293.7 g of an aqueous solution of tetramethylammonium bicarbonate (containing 42.4% by mass as tetramethylammonium hydroxide) was diluted with 111.5 g of pure water. While stirring, 168.4 g of zirconium oxycarbonate powder (containing 40.1% by mass as ZrO) was gradually added. After the addition was complete, the mixture was heated to 85°C, and 9.6 g of metastannic acid (containing 86.0% by mass as SnO) was gradually added. The mixture was then aged at 105°C for 5 hours, followed by a hydrothermal treatment at 145°C for 5 hours. The sol was then washed and concentrated in an ultrafiltration apparatus while adding pure water. The resulting sol was an aqueous dispersion of alkaline zirconium oxide-stannic oxide composite oxide colloidal particles (T1-1). It had a pH of 9.4, a total metal oxide concentration (total of ZrO and SnO) of 5.0% by mass, and an average particle size (measured by dynamic light scattering) of 15 nm.

[0079] (Reference example 2) Preparation of silicon dioxide-stannic oxide colloidal particles (T2-1) for coating 77.2 g of JIS No. 3 sodium silicate (containing 29.8% by mass, calculated as SiO2) was dissolved in 668.8 g of purified water, followed by the dissolution of 20.9 g of sodium stannate NaSnO3·H2O (containing 55.1% by mass, calculated as SnO2). The resulting aqueous solution was passed through a column packed with a hydrogen-type cation exchange resin (Amberlite® IR-120B). 7.2 g of diisopropylamine was then added to the resulting aqueous dispersion sol. The resulting sol was an alkaline aqueous dispersion sol of silicon dioxide-stannic oxide composite oxide colloidal particles (T2-1), with a pH of 8.0, a total metal oxide concentration (SnO2 and SiO2) of 1.7% by mass, and an average primary particle diameter of 1 to 4 nm as determined by transmission electron microscopy.

[0080] (Reference example 3) Preparation of stannic oxide core colloidal particles (T1-2) 64.0 g of oxalic acid dihydrate (45.7 g in terms of oxalic acid) was dissolved in 723.3 g of purified water and heated to 70°C with stirring. Then, 290.3 g of 35% hydrogen peroxide and 128.1 g of metallic tin powder (99.7% SnO2 content) were added. The hydrogen peroxide and metallic tin were added alternately in 10 separate additions. First, 29.0 g of 35% hydrogen peroxide was added, followed by 12.8 g of metallic tin. This procedure was repeated after waiting for the reaction to complete (10 to 15 minutes). The addition took 2 hours. After the addition, the solution was heated for 2 hours while maintaining the liquid temperature at 90°C to terminate the reaction. Next, 394.5 g of 35% hydrogen peroxide was added, and the mixture was kept at 90°C for 5 hours. Next, 5.1 g of isopropylamine was added, and the mixture was kept at 50°C for 3 hours, after which the mixture was passed through a column packed with 500 mL of anion exchange resin (Amberlite® IRA-410). The resulting sol was an aqueous dispersion of alkaline stannic oxide composite oxide colloidal particles (T1-2), with a pH of 11.0, an SnO2 concentration of 4.0 mass%, and an average particle size (dynamic light scattering particle size) of 20 nm.

[0081] (Reference example 4) Preparation of titanium dioxide-stannic oxide composite colloidal particles (T1-3) as core particles 319.5 g of 25 mass% tetramethylammonium hydroxide aqueous solution was dissolved in 947.1 g of pure water, and then 14.8 g of metastannic acid (containing 12.5 g in terms of SnO2), 236.6 g of titanium tetraisopropoxide (containing 66.6 g in terms of TiO2), and oxalic acid dihydrate were added. To the resulting solution, 82.0 g of the product (58.5 g in terms of oxalic acid) was added under stirring. The mixed solution was maintained at 80°C for 2 hours, then further reduced to 580 Torr and maintained for 2 hours to prepare a mixed solution. The mixed solution was placed in a glass-lined autoclave and subjected to hydrothermal treatment at 140°C for 5 hours. After cooling to room temperature, the solution was removed. The resulting sol was an aqueous dispersion sol of acidic titanium oxide-stannic oxide composite oxide colloidal particles (T1-3), with a pH of 3.9, a total metal oxide concentration (TiO2 and SnO2) of 5.0 mass%, and an average particle size (dynamic light scattering particle size) of 16 nm. The resulting sol was dried at 110°C, and the powder was subjected to X-ray diffraction analysis, confirming that it was a rutile crystal.

[0082] (Production Example 1) Preparation of colloidal particles (T3-1) of zirconium oxide-stannic oxide composite oxide modified with silicon dioxide-stannic oxide composite oxide 830.4 g of the aqueous dispersion sol of alkaline silicon dioxide-stannic oxide composite oxide colloidal particles (T2-1) prepared in Reference Example 2 was added under stirring to 1411.7 g of the aqueous dispersion sol of alkaline zirconium oxide-stannic oxide composite oxide colloidal particles (T1-1) obtained in Reference Example 1. The mixture was then heated to 95°C and maintained for 2 hours, after which it was passed through a column packed with a hydrogen-type cation exchange resin (Amberlite (registered trademark) IR-120B), and the aqueous dispersion sol after passing through was concentrated by ultrafiltration membrane method. The dispersion medium of the resulting aqueous sol was then replaced with methanol using a rotary evaporator to obtain a methanol-dispersed sol of zirconium oxide-stannic oxide composite oxide colloidal particles (T3-1) modified with silicon dioxide-stannic oxide composite oxide. This methanol-dispersed sol had a pH of 5.0, a total metal oxide (ZrO2, SnO2, and SiO2) concentration of 38.5% by mass, a viscosity of 3.3 mPa s, and an average particle size (measured by dynamic light scattering (DLS)) of 20 nm.

[0083] (Production Example 2) Preparation of colloidal particles of zirconium oxide-stannic oxide composite oxide (T3-2) modified with silicon dioxide-stannic oxide composite oxide, in which an organosilicon compound having an acryloxy group is bonded to the surface. To 155.8 g of the methanol-dispersed sol of zirconium oxide-stannic oxide composite oxide colloidal particles (T3-1) modified with silicon dioxide-stannic oxide composite oxide obtained in Production Example 1, 44.2 g of methanol was added. Next, 3.8 g of 3-acryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBM5103) was added with stirring, and the mixture was refluxed at 70°C for 5 hours to obtain a methanol-dispersed sol of zirconium oxide-stannic oxide composite oxide colloidal particles (T3-2) modified with silicon dioxide-stannic oxide composite oxide, in which an organosilicon compound having an acryloxy group was bonded to the surface. This methanol-dispersed sol had a total metal oxide (ZrO, SnO, and SiO) concentration of 30.5% by mass, a viscosity of 2.4 mPa·s, and an average particle size (dynamic light scattering particle size) of 25 nm as measured by dynamic light scattering (DLS).

[0084] (Production Example 3) Preparation of colloidal particles of zirconium oxide-stannic oxide composite oxide (T3-3) modified with silicon dioxide-stannic oxide composite oxide, in which organosilicon compounds having ureido groups are bonded to the surface. 44.2 g of methanol was added to 155.8 g of the methanol dispersion sol of zirconium oxide-stannic oxide composite oxide colloidal particles (T3-1) modified with silicon dioxide-stannic oxide composite oxide obtained in Production Example 1. 7.3 g of a methanol solution of ureidopropyltriethoxysilane (50% by mass, KBE585, manufactured by Shin-Etsu Chemical Co., Ltd.) was added with stirring, and the mixture was refluxed at 70°C for 5 hours. After a reduced pressure concentration step using an evaporator, a silicon dioxide-stannic oxide composite dispersion sol was obtained in which an organosilicon compound having a ureido group was bonded to the surface. A methanol dispersion sol of zirconium oxide-stannic oxide composite oxide colloidal particles (T3-3) modified with composite oxides was obtained. This methanol dispersion sol had a total metal oxide (ZrO2, SnO2, and SiO2) concentration of 30.5 mass%, a viscosity of 2.3 mPa s, and an average particle size (Dynamic Light Scattering particle size) of 24 nm as measured by dynamic light scattering (DLS).

[0085] (Production Example 4) Preparation of colloidal particles of zirconium oxide-stannic oxide composite oxide (T3-4) modified with silicon dioxide-stannic oxide composite oxide, in which organosilicon compounds having glycidyl groups are bonded to the surface. To 155.8 g of the methanol-dispersed sol of zirconium oxide-stannic oxide composite oxide colloidal particles (T3-1) modified with silicon dioxide-stannic oxide composite oxide obtained in Production Example 1, 44.2 g of methanol was added. 3.9 g of a methanol solution of 3-glycidoxypropyltriethoxysilane (50% by mass, KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.) was added with stirring, and the mixture was refluxed at 70°C for 5 hours to obtain a methanol-dispersed sol of zirconium oxide-stannic oxide composite oxide colloidal particles (T3-4) modified with silicon dioxide-stannic oxide composite oxide, which had an organosilicon compound having glycidyl groups bonded to its surface. This methanol-dispersed sol had a total metal oxide (ZrO, SnO, and SiO) concentration of 30.5% by mass, a viscosity of 2.3 mPa·s, and an average particle size (dynamic light scattering particle size) of 22 nm as measured by dynamic light scattering (DLS).

[0086] (Production Example 5) Preparation of stannic oxide colloidal particles (T3-5) modified with silicon dioxide-stannic oxide composite oxide To 1,458.8 g of the aqueous dispersion sol of stannic oxide colloidal particles (T1-2) obtained in Reference Example 3, 514.9 g of the aqueous dispersion sol of alkaline silicon dioxide-stannic oxide composite oxide colloidal particles (T2-1) prepared in Reference Example 2 was added under stirring. The mixture was then heated to 95°C and maintained for 2 hours, after which the mixture was passed through a column packed with a hydrogen-type cation exchange resin (Amberlite (registered trademark) IR-120B). The aqueous dispersion sol after passing through was then concentrated by ultrafiltration membrane method. The dispersion medium of the resulting aqueous sol was then replaced with methanol using a rotary evaporator to obtain a methanol-dispersed sol of stannic oxide colloidal particles (T3-5) modified with silicon dioxide-stannic oxide composite oxide. This methanol-dispersed sol had a total metal oxide (SnO2 and SiO2) concentration of 30.5 mass%, a viscosity of 1.3 mPa s, and an average particle size (measured by dynamic light scattering (DLS)) of 18 nm.

[0087] (Production Example 6) Preparation of titanium dioxide-stannic oxide-zirconium oxide composite oxide colloidal particles (T3-6) modified with silicon dioxide-stannic oxide composite oxide 82.7 g of zirconium oxychloride (containing 21.2% by mass, calculated as ZrO) was diluted with 501.1 g of pure water to prepare 583.8 g of an aqueous zirconium oxychloride solution (containing 3.0% by mass, calculated as ZrO). 1516.2 g of an aqueous dispersion sol of titanium oxide-stannic oxide composite oxide colloidal particles (T1-3) prepared in Reference Example 4 was added under stirring. Hydrolysis was then carried out by heating to 95°C, yielding an aqueous dispersion sol of titanium oxide-stannic oxide-zirconium oxide composite oxide colloidal particles with a thin zirconium oxide layer formed on the surface. 2041.2 g of the resulting aqueous dispersion sol was added under stirring to 1763.3 g of an aqueous dispersion sol of alkaline silicon dioxide-stannic oxide composite oxide colloidal particles (T2-1) prepared in Reference Example 2, and the resulting solution was passed through a column packed with 500 mL of anion exchange resin (Amberlite® IRA-410, manufactured by Organo Corporation). The aqueous dispersion sol after passing the liquid was then heated at 95°C for 3 hours and concentrated by ultrafiltration membrane method. Next, the dispersion medium of the obtained water-dispersed sol was evaporated in methanol using a rotary evaporator. A methanol-dispersed sol of titanium dioxide-stannic oxide-zirconium oxide composite oxide colloidal particles (T3-6) modified with silicon dioxide-stannic oxide composite oxide was obtained. This methanol-dispersed sol had a pH of 5.2, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5 mass%, a viscosity of 1.8 mPa s, and an average particle size (measured by dynamic light scattering (DLS)) of 20 nm.

[0088] Example 1 (Preparation of Coating Composition) A glass vessel equipped with a magnetic stirrer was charged with 62.4 parts by mass of 3-glycidoxypropyltrimethoxysilane (KBM403 manufactured by Shin-Etsu Chemical Co., Ltd.), 8.1 parts by mass of tetraethoxysilane (Tokyo Chemical Industry Co., Ltd.), 3.8 parts by mass of X-12-1154 (manufactured by Shin-Etsu Chemical Co., Ltd.), and 26.2 parts by mass of methanol, and 18.6 parts by mass of 0.01 N hydrochloric acid was added dropwise over 3 hours while stirring at room temperature (20°C). After completion of the dropwise addition, the mixture was stirred at room temperature (20°C) for 0.5 hours to obtain a partial hydrolyzate of 3-glycidoxypropyltrimethoxysilane, tetraethoxysilane, and X-12-1154. Next, 25.4 parts by weight of methanol, 45.7 parts by weight of propylene glycol monomethyl ether, 96.8 parts by weight of a methanol dispersion sol (containing 38.5% by weight of total metal oxides) of the zirconium oxide-stannic oxide composite oxide colloidal particles (T3-1) modified with silicon dioxide-stannic oxide composite oxide obtained in Production Example 1, and 6.1 parts by weight of aluminum acetylacetonate as a curing agent were added to 119.0 parts by weight of the partial hydrolyzate of 3-glycidoxypropyltrimethoxysilane and tetraethoxysilane (trade name X-12-1154) and thoroughly stirred to prepare a hard coat coating liquid (coating composition). The mass ratio of (S2-1-1):(S2-1-2) was 1:7.7, and the mass ratio of (S1):(S2) was 5.1:94.9. (Formation and evaluation of cured film) Urethane plastic lens (refractive index n D A hard coat coating liquid (coating composition) was applied to a substrate (H=1.60) and a glass substrate by dip coating (film thickness: 3 μm). The solvent was evaporated at 80°C for 10 minutes, and then the substrate was heated at 120°C for 2 hours to harden the coating film, forming an optical element having a hardened film. The tests (1) to (6) above were carried out, and the evaluation results are shown in Table 1.

[0089] Example 2 Except for changing the amount of 3-glycidoxypropyltrimethoxysilane added to 59.0 parts by mass and the amount of product X-12-1154 added to 7.5 parts by mass, the preparation of a coating composition and the formation and evaluation of a cured film were carried out in the same manner as in Example 1. The mass ratio of (S2-1-1):(S2-1-2) was 1:7.28, and the mass ratio of (S1):(S2) was 10.1:89.9.

[0090] Example 3 Except for changing the amount of 3-glycidoxypropyltrimethoxysilane added to 52.0 parts by mass and the amount of product X-12-1154 added to 15.0 parts by mass, the preparation of a coating composition and the formation and evaluation of a cured film were carried out in the same manner as in Example 1. The mass ratio of (S2-1-1):(S2-1-2) was 1:6.42, and the mass ratio of (S1):(S2) was 20.0:80.0.

[0091] Example 4 In Example 2, the procedure was the same as in Example 2 until a partial hydrolysis product of 3-glycidoxypropyltrimethoxysilane, tetraethoxysilane, and product name X-12-1154 was obtained. Next, 45.7 parts by mass of propylene glycol monomethyl ether and the silicon dioxide-based oxide composite obtained in Production Example 2, in which an organosilicon compound having an acryloxy group is bonded to the surface, were obtained. A methanol dispersion sol (122.2 parts by mass) of zirconium oxide-stannic oxide composite oxide colloidal particles (T3-2) modified with tin oxide (30.5% by mass in terms of total metal oxides) and 6.1 parts by mass of aluminum acetylacetonate as a curing agent were added to 119.0 parts by mass of the partial hydrolyzate of 3-glycidoxypropyltrimethoxysilane and tetraethoxysilane (trade name X-12-1154) described above, and the mixture was thoroughly stirred to prepare a hard coat coating liquid (coating composition). The formation and evaluation of the cured film were carried out in the same manner as in Example 1. The mass ratio of (S2-1-1):(S2-1-2) was 1:7.28, and the mass ratio of (S1):(S2) was 10.1:89.9.

[0092] Example 5 In Example 4, a coating composition was prepared and a cured film was formed and evaluated in the same manner as in Example 4, except that a methanol dispersion sol (containing 30.5 mass% in terms of total metal oxides) of zirconium oxide-stannic oxide composite oxide colloidal particles (T3-3) modified with silicon dioxide-stannic oxide composite oxide, the surfaces of which were bonded to organosilicon compounds having ureido groups, obtained in Production Example 3, was used instead of the colloidal particles (T3-2) obtained in Production Example 2. The mass ratio of (S2-1-1):(S2-1-2) was 1:7.28, and the mass ratio of (S1):(S2) was 10.1:89.9.

[0093] Example 6 In Example 4, a coating composition was prepared and a cured film was formed and evaluated in the same manner as in Example 4, except that a methanol dispersion sol (containing 30.5 mass% in terms of total metal oxides) of zirconium oxide-stannic oxide composite oxide colloidal particles (T3-4) modified with silicon dioxide-stannic oxide composite oxide, the surfaces of which were bonded to organosilicon compounds having glycidyl groups, obtained in Production Example 4, was used instead of the colloidal particles (T3-2) obtained in Production Example 2. The mass ratio of (S2-1-1):(S2-1-2) was 1:7.28, and the mass ratio of (S1):(S2) was 10.1:89.9.

[0094] Example 7 In Example 4, a coating composition was prepared and a cured film was formed and evaluated in the same manner as in Example 4, except that a methanol dispersion sol (containing 30.5% by mass, calculated as total metal oxides) of stannic oxide colloidal particles (T3-5) modified with silicon dioxide-stannic oxide composite oxide obtained in Production Example 5 was used instead of the colloidal particles (T3-2) obtained in Production Example 2. The mass ratio of (S2-1-1):(S2-1-2) was 1:7.28, and the mass ratio of (S1):(S2) was 10.1:89.9.

[0095] Example 8 (Preparation of Coating Composition) A glass vessel equipped with a magnetic stirrer was charged with 49.1 parts by mass of 3-glycidoxypropyltrimethoxysilane (KBM403 manufactured by Shin-Etsu Chemical Co., Ltd.), 6.7 parts by mass of tetraethoxysilane (Tokyo Chemical Industry Co., Ltd.), 6.3 parts by mass of X-12-1154 (manufactured by Shin-Etsu Chemical Co., Ltd.), and 17.9 parts by mass of methanol, and 14.7 parts by mass of 0.01 N hydrochloric acid was added dropwise over 3 hours while stirring at room temperature (20°C). After the dropwise addition, the mixture was stirred at room temperature (20°C) for 0.5 hours to obtain a partial hydrolyzate of 3-glycidoxypropyltrimethoxysilane, tetraethoxysilane, and X-12-1154. Next, 45.7 parts by mass of propylene glycol monomethyl ether, 147.9 parts by mass of a methanol dispersion sol of titanium oxide-stannic oxide-zirconium oxide composite oxide colloidal particles (T3-6) modified with silicon dioxide-stannic oxide composite oxide obtained in Production Example 6 (containing 30.5% by mass in terms of total metal oxides), 4.8 parts by mass of aluminum acetylacetonate as a curing agent, and 94.6 parts by mass of the partial hydrolyzate of the above-mentioned 3-glycidoxypropyltrimethoxysilane, tetraethoxysilane (trade name X-12-1154) were added. The mixture was added and thoroughly stirred to prepare a coating liquid for hard coating (coating composition). The mass ratio of (S2-1-1):(S2-1-2) was 1:7.33, and the mass ratio of (S1):(S2) was 10.1:89.9. (Formation and evaluation of cured film) Urethane plastic lens (refractive index n D Formation and evaluation of a cured film were carried out in the same manner as in Example 1, except that a cured film having a viscosity of 1000 MPa (=1.67) was used.

[0096] Comparative Example 1 In Example 1, the amount of 3-glycidoxypropyltrimethoxysilane added was changed to 65.9 parts by mass, and X-12-1154 (trade name) was not added. The preparation of a coating composition and the formation and evaluation of a cured film were carried out in the same manner as in Example 1.

[0097] Comparative Example 2 Preparation of a coating composition and formation and evaluation of a cured film were carried out in the same manner as in Example 2, except that KR-518 (manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of X-12-1154. The product name KR-518 has an alkoxy group (a combination of a methoxy group and an ethoxy group) and a mercapto group as a side chain on the main chain of polysiloxane, and the amount of alkoxy groups is 50% by mass, and the viscosity is 20 mm. 2 / s, and a mercapto group equivalent of 800 g / mol.

[0098] Comparative Example 3 Preparation of a coating composition and formation and evaluation of a cured film were carried out in the same manner as in Example 2, except that KR-519 (manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of X-12-1154. The product name KR-519 has an alkoxy group (methoxy group) and an organic functional group (mercapto group and methyl group) in the main chain of polysiloxane, and the amount of alkoxy groups is 30% by mass, and the viscosity is 5 mm. 2 / s, and the reactive functional group (mercapto group) equivalent was 450 g / mol.

[0099] [Table 1] In addition, the refractive index measurement of Comparative Example 3 was not possible because the reflectance was significantly reduced.

[0100] In all of Examples 1 to 8, after preparation of the hard coat coating liquid, the liquid did not undergo gelation or phase separation, and it was confirmed that the liquid was a coating composition with excellent stability. Furthermore, as shown in Table 1, in all of Examples 1 to 8, the optical components having a cured film, which was a cured product of the hard coat coating liquid (coating composition), exhibited excellent adhesion of the cured film to the substrate, appearance after a weather resistance test, adhesion after a weather resistance test, scratch resistance, and transparency.

[0101] On the other hand, Comparative Example 1 was inferior to the Examples in adhesion and adhesion after the weather resistance test, Comparative Example 2 was inferior to the Examples in terms of change in appearance after the weather resistance test, and Comparative Example 3 was inferior to the Examples in terms of transparency. [Industrial Applicability]

[0102] The coating composition of the present invention provides a cured film having excellent adhesion to a substrate, excellent appearance after a weathering test, excellent adhesion after a weathering test, excellent scratch resistance, and excellent transparency, and is applicable to eyeglass lenses, camera lenses, automobile window glass, computer displays, television displays, mobile terminal displays, etc.

Claims

1. A coating composition comprising the following components (S) and (T): the component (S) is a silane compound, a hydrolysate thereof, or a mixture thereof, the silane compound contains a polymeric silane coupling agent as a component (S1), the polymeric silane coupling agent has an alkoxysilyl group and a mercapto group as side chains on a main chain of an organic compound, the molar ratio of (mercapto group) to (alkoxysilyl group), that is, (mercapto group) / (alkoxysilyl group), is 2 to 6, and the mercapto group equivalent is in a ratio of 150 g / mol to 300 g / mol, The component (T) is an organic solvent dispersion sol of colloidal particles (T3) formed of modified metal oxide colloidal particles having an average particle size of 2 nm to 100 nm, the surfaces of which are coated with a coating (T2) consisting of colloidal particles of an acidic oxide having an average primary particle size of 1 nm to 4 nm, the colloidal particles (T1) being a core of a metal oxide having an average particle size of 2 nm to 60 nm, A coating composition comprising the component (S):component (T) in a mass ratio of 100:10 to 500.

2. 2. The coating composition according to claim 1, wherein the alkoxysilyl group on the side chain of the polymeric silane coupling agent of component (S1) is a trimethoxysilyl group, the molar ratio of (mercapto group) to (alkoxysilyl group), (mercapto group) / (alkoxysilyl group), is 3 to 5, and the mercapto group equivalent is 200 g / mol to 250 g / mol.

3. The silane compound of the component (S) further contains, as the component (S2), (S2-1): 【Chemistry 1】 (in formula (1), R1 is an alkyl group, an aryl group, a halogenated alkyl group, a halogenated aryl group, an alkoxyaryl group, an alkenyl group, or an organic group having an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a ureido group, or a cyano group, and is bonded to a silicon atom via a Si-C bond; R2 is an alkoxy group, an acyloxy group, or a halogen atom; and a is an integer of 0 to 3), and (S2-2): 【Chemistry 2】 (in formula (2), R3 is an alkyl group and is bonded to a silicon atom through a Si-C bond; R4 is an alkoxy group, an acyloxy group, or a halogen atom; Y is an alkylene group, an arylene group, an NH group, or an oxygen atom; b is an integer of 0 to 3; and c is an integer of 0 or 1).

4. The component (S2) is a silane compound in which a is 0 in the formula (1) as the component (S2-1-1), and the component (S2-1-2) is a silane compound in which a is 1 in the formula (1) as the component (S2-1-2). 1 (S2-1-1):(S2-1-2) is a silane coupling agent in which a is 1 in formula (1) and contains an epoxy group, or a silane coupling agent in which a is 1 in formula (1) and contains a (meth)acryloyl group, or a mixture thereof, and the mass ratio of (S2-1-1):(S2-1-2) is in the range of 1:1 to 1:

25.

5. 4. The coating composition according to claim 3, comprising (S1):(S2) in a mass ratio of 5:95 to 30:

70.

6. 6. The coating composition according to claim 1, wherein the colloidal particles (T1) are an oxide of at least one metal selected from the group consisting of Ti, Fe, Cu, Zn, Y, Zr, Nb, Mo, In, Sn, Sb, Ta, W, Pb, Bi and Ce.

7. 7. The coating composition according to claim 1, wherein the coating (T2) is an oxide of at least one metal selected from the group consisting of Si, Zr, Sn, Mo, Sb and W.

8. The coating composition according to any one of claims 1 to 7, wherein the colloidal particles (T1) are a metal oxide consisting of tin oxide-zirconium oxide, or a metal oxide consisting of titanium oxide-tin oxide-zirconium oxide, and the coating (T2) is a metal oxide consisting of tin oxide-silicon dioxide.

9. 9. The coating composition according to claim 1, wherein the surface of the component (T2) is coated with a (meth)acryloyloxytrialkoxysilane, a ureidopropyltrialkoxysilane, or a glycidoxypropyltrialkoxysilane.

10. The coating composition according to any one of claims 1 to 9, wherein component (T) further comprises an amine.

11. The coating composition according to any one of claims 1 to 10, further comprising a metal chelate or a perchlorate as a curing agent.

12. The coating composition according to any one of claims 1 to 11, further comprising a surfactant.

13. An optical member having a cured film formed on the surface of an optical substrate from the coating composition according to any one of claims 1 to 12.

14. The optical member according to claim 13, further comprising an anti-reflection film on the surface thereof.

15. (a) a step of preparing a silane compound, a hydrolyzate thereof, or a mixture thereof as a component (S); and A method for producing a coating composition, comprising the step (b) of mixing the component (S) obtained in the step (a) with the following component (T), the silane compound includes a polymeric silane coupling agent as a component (S1), the polymeric silane coupling agent having an alkoxysilyl group and a mercapto group as side chains on a main chain of an organic compound, the molar ratio of the (mercapto group) to the (alkoxysilyl group), that is, (mercapto group) / (alkoxysilyl group), being 2 to 6, and containing a mercapto group equivalent in a ratio of 150 g / mol to 300 g / mol; The component (T) is an organic solvent dispersion sol of colloidal particles (T3) formed of modified metal oxide colloidal particles having an average particle size of 2 nm to 100 nm, the surfaces of which are coated with a coating (T2) consisting of acidic oxide colloidal particles having an average primary particle size of 1 nm to 4 nm, said component (T1) being a core of colloidal particles of a metal oxide having an average particle size of 2 nm to 60 nm.

Citation Information

Patent Citations

  • Method of producing porous material

    JP1977011261A

  • Coating composition

    JP1978111336A

  • Polymer-grafted colloidal silica, polymer-grafted colloidal silica dispersion and its manufacturing method

    JP2008100894A

  • Multilayer coating film forming method

    JP2019005727A

  • Coating composition and optical member

    WO2015115377A1